Opioid-induced sexual dysfunction in men - Salata, Bartłomiej; Toczek-Wasiak, Agnieszka; Kluczna, Agnieszka; Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2022)
Sexuality is an important part of life, also for patients approaching death. However, sexual functions may be reduced in this group of patients due to the underlying disease, its symptoms, concomitant diseases, and treatment. Opioids, widely used in palliative care, may be a significant aetiological factor, influencing sexual functions probably mainly by the impact on the hypothalamus-pituitary-gonadal axis, expressed in erectile dysfunction, lack of desire and arousal, and lowered overall sexual satisfaction. Scarce evidence causes difficulties in identifying opioids causing sexual dysfunctions to a lesser extent. Probably buprenorphine, tapentadol, tramadol, and short-acting opioids should be recommended. Based on little and weak evidence, the therapeutic options are testosterone replacement therapy, bupropion, trazodone, opioid antagonist, and ginseng. The common multimorbidity of palliative patients leads to considering also of other aetiological factors and individualized treatment, as well as complicate deducting the importance of opioids in inducing sexual dysfunctions.